Third-Party Payers…. The Silver Bullet? - Gosalia, Amit (Seminars in Hearing, 2019)
Healthcare reform brought about many changes in the healthcare industry including the hearing aid delivery model. Third-party payers (TPPs) became a growing trend with health insurance companies. The traditional hearing aid delivery model changed from provider and patient to provider, TPP, and patient. Due to the insertion of this middle man, profit can be diminished from the hearing aid sale, along with processes. Based on this decrease in revenue, decisions need to be made if using a TPP is profitable or even affordable for a clinic. Recent polls indicate more than half of those clinics polled currently do not participate with TPPs.
Keywords: third-party payer; private pay; dispensing fees; hearing aids; healthcare reform